Asserting the visibility of social work in science - Munté-Pascual, Ariadna; Matulič-Domandzič, María Virginia; López de Aguileta, Ane; Aiello, Emilia; Elboj, Carmen; Valero, Diana; Melgar, Patricia (Frontiers in Sociology, 2024)
Scientific evidence has shown that Social Work has frequently been considered a second-level discipline in the traditional sexist hierarchy, because pioneers and most social workers are women. The twofold objective of this article is to analyze the dynamics that overcome this consideration and to put forward actions to go further in the near future. The factors that limit these actions and those that make them possible are studied. This article exposes the dynamics of the current transformation of Social Work, namely, the increase in the importance of social impact in social research, the increase in interdisciplinarity, and the impact of interdisciplinary research.